A Zakat Accounting Standard (ZAS) for Malaysian companies - Abu Bakar, Nur Barizah (Association of Muslim Social Scientists, 2007)
This paper focuses on the need to harmonize the practice of zakat on companies throughout Malaysia by implementing a zakat accounting standard (ZAS). The objectives of this paper are fourfold: (1) to highlight the current practice of zakat on companies in Malaysia; (2) discuss the usefulness of AAOIFI FAS 9, MASB FRS i-1, and MASB TR i-1 as guidelines for developing a ZAS; (3) suggest a collaboration by various parties designed to pool initiatives, knowledge, and skills to develop a useful and favorable ZAS; and (4) to demonstrate that without proper education and a strong political will, there is a little hope of making any ZAS a reality.